Gene-centric association signals for haemostasis and thrombosis traits identified with the HumanCVD BeadChip - Gaunt, Tom R.; Zabaneh, Delilah; Shah, Sonia; Guyatt, Anna; Ladroue, Christophe; Kumari, Meena; Drenos, Fotios; Shah, Tina; Talmud, Philippa J.; Casas, Juan Pablo; Lowe, Gordon; Rumley, Ann; Lawlor, Debbie A.; Kivimaki, Mika; Whittaker, John; Hingorani, Aroon D.; Humphries, Steve E.; Day, Ian N. (Thrombosis and Haemostasis, 2013)
Coagulation phenotypes show strong intercorrelations, affect cardiovascular disease risk and are influenced by genetic variants. The objective of this study was to search for novel genetic variants influencing the following coagulation phenotypes: factor VII levels, fibrinogen levels, plasma viscosity and platelet count. We genotyped the British Women’s Heart and Health Study (n=3,445) and the Whitehall II study (n=5,059) using the Illumina HumanCVD BeadArray to investigate genetic associations and pleiotropy. In addition to previously reported associations (SH2B3, F7/F10, PROCR, GCKR, FGA/FGB/FGG, IL5), we identified novel associations at GRK5 (rs10128498, p = 1.30×10−6), GCKR (rs1260326, p = 1.63×10−6), ZNF259-APOA5 (rs651821, p = 7.17x10–6) with plasma viscosity; and at CSF1 (rs333948, p = 8.88×10−6) with platelet count. A pleiotropic effect was identified in GCKR which associated with factor VII (p = 2.16×10−7) and plasma viscosity (p = 1.63×10−6), and, to a lesser extent, ZNF259-APOA5 which also associated with factor VII and fibrinogen (p<1.00×10−2) and plasma viscosity (p<1.00×10−5). Triglyceride associated variants were overrepresented in factor VII and plasma viscosity associations. Adjusting for triglyceride levels resulted in attenuation of associations at the GCKR and ZNF259-APOA5 loci. In addition to confirming previously reported associations, we identified four single nucleotide polymorphisms (SNPs) associated with plasma viscosity and platelet count and found evidence of pleiotropic effects with SNPs in GCKR and ZNF259-APOA5. These triglyceride-associated, pleiotropic SNPs suggest a possible causal role for triglycerides in coagulation.
Keywords: Haemostasis; thrombosis; HumanCVD; clotting factors; genetic association